Biochemical and Clinical Variables of Normal Parathyroid and Hyperparathyroid Diabetic Chronic Kidney Disease Patients (Journal of Enam Medical College, 2016)
Background: In chronic kidney disease (CKD) intact parathyroid hormone (iPTH) level is often increased before clinical hyperphosphatemia occurs. Despite its importance very few studies evaluated parathyroid status in CKD.Objective: The study was undertaken to estimate level of parathormone in diabetic CKD patients at a tertiary level hospital and assessing its relationship with different parameters like hemoglobin, calcium etc. and comparing biochemical and clinical variables between normal parathyroid and hyperparathyroid groups.Materials and Methods: It was a hospital based cross-sectional study involving purposively selected chronic kidney disease patients attending nephrology and endocrinology outdoor and indoor services of BIRDEM hospital, Dhaka, Bangladesh. Study was conducted during the period of April to October 2010. All the subjects were divided into two groups based on serum parathormone level and different parameters were compared between groups.Results: The mean duration of chronic kidney disease was significantly higher in hyperparathyroid group than that in the normal group (